2012
DOI: 10.1038/ncomms1711
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional and temporal controls of three-dimensional cell migration by zyxin and binding partners

Abstract: Spontaneous molecular oscillations are ubiquitous in biology. But to our knowledge, periodic cell migratory patterns have not been observed. Here we report the highly regular, periodic migration of cells along rectilinear tracks generated inside three-dimensional matrices, with each excursion encompassing several cell lengths, a phenotype that does not occur on conventional substrates. Short hairpin RNA depletion shows that these one-dimensional oscillations are uniquely controlled by zyxin and binding partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
95
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 52 publications
7
95
0
Order By: Relevance
“…To our knowledge, there has been only one complex model that may be appropriate for addressing cellular oscillations (65,66). However, the main purpose of the study was to explore the range of possible cell behaviors as a result of the interplay between shape, mechanics, and polarity, with oscillation demonstrated as one of the possible behaviors without considering the trigger or underlying control circuit.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there has been only one complex model that may be appropriate for addressing cellular oscillations (65,66). However, the main purpose of the study was to explore the range of possible cell behaviors as a result of the interplay between shape, mechanics, and polarity, with oscillation demonstrated as one of the possible behaviors without considering the trigger or underlying control circuit.…”
Section: Discussionmentioning
confidence: 99%
“…where n is the dimension of the extracellular space (which can be 1D, 2D, and 3D) (10,17,26,27), and τ is the time lag between positions of the cell. The autocorrelation function of the cell velocity vector for the PRW model exhibits a single exponential decay…”
Section: Significancementioning
confidence: 99%
“…However, cell migration in vivo often forces cells to remodel, exert pulling forces on, and move through a 3D collagen I-rich matrix. Recent work has demonstrated that mechanisms of 3D migration are often different from their 2D counterparts (9)(10)(11)(12)(13)(14)(15). Migration on 2D dishes, which induces a basal-apical polarization of the cell, is driven by actomyosin contractility of stress fibers between large focal adhesions and the formation of a wide lamellipodium terminated by thin filopodial protrusions at the leading cellular edge (4,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…79 Additionally, recent data indicate that zyxin and Cas cooperate to ensure efficient cell migration in three-dimensional cultures. 80 Intravasation of tumor cells into the cardiovascular and lymphatic systems requires invasion through the basement membrane and vessel walls. Invadopodia formation and protease activity play key roles in intravasation, and as discussed in the preceding section, Cas/NEDD9 signaling is important for both of these processes (see Fig.…”
Section: Monographsmentioning
confidence: 99%